A Multidimensional Qualitative Approach: Synthesizing Western and Islamic Research Paradigms - Rahman, Abdul; Sesmiarni, Zulfani; Dina, Hidayatul; Julhadi, Julhadi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
This study aims to present a comprehensive synthesis of four major qualitative research approaches narrative inquiry, phenomenology, grounded theory, and Islamic research design as a multidimensional framework for studying phenomena in Islamic education. Narrative inquiry emphasizes the reconstruction of life stories as sources of meaning; phenomenology seeks to uncover the essence of participants’ lived experiences; grounded theory systematically generates concepts or theories emerging from empirical data; while Islamic research design integrates contemporary qualitative strategies with Islamic epistemology, ethics, and values. The analysis demonstrates that each approach offers distinctive strengths yet remains compatible for integrative use. Narrative inquiry supports studies requiring an exploration of individual life trajectories, phenomenology is suitable for examining spiritual and religious experiences in depth, grounded theory is relevant for developing contextually rooted theoretical constructs, and Islamic research design ensures that the research process aligns with Islamic ethical and epistemological foundations. Taken together, these approaches form a multidimensional qualitative model that enriches methodological discourse in Islamic studies and promotes research practices that are both contextually grounded and aligned with the needs of contemporary Muslim societies.